Assessment of the Roadway Dynamic Response Due to the Tatra 815 Lorry Excitation and Experimental Verification - Valaskova, Veronika; Papan, Daniel; Barros, Rui C. (Communications - Scientific letters of the University of Zilina, 2016)
The effect of moving load represents the current problem which is analyzed in engineering practice. The response of the vehicle and its dynamic effect on the pavement can be analyzed in an experimental or computational way. The road-vehicle interaction effect is one of the most important problems for the vibration propagation due to traffic. This paper shows the practical analysis of the Tatra 815 Lorry passing effect using two software systems based on the Finite Element Method (FEM). First system is better for a vehicle model and its passing on a simple road model based on Winkler-Pasternak theory of elastic half-space. In the second system, the vehicle model is not supported but it is better and more accurate for the road and geological environment model - where the subsoil layers were modeled separately. The computing is carried out in time domain. The results obtained by the FEM simulation are compared with the result obtained by the experiment in frequency domain.